Self-regulated learning: A key factor in the effectiveness of online learning for second language learners - Yu, Bo (Frontiers in Psychology, 2023)
Self-regulated Learning (SRL) is an important factor determining the effectiveness of learners' online learning. This review explores self-regulated learning theories of second language learners, as well as the influencing factors in an online learning environment. It is found that the learners' language learning beliefs, language level, learning motivation and other factors affect their self-regulated learning in the technical environment. In addition, from the external environment, guiding and intervening in the online learning process of learners will also affect their self-regulated ability.The pedagogical implications for teachers are also given at the end.